Acceptance of childhood and adolescent vaccination against COVID-19 in France: a national cross-sectional study in May 2021. Issue 12 (2nd December 2021) - Verger, Pierre; Peretti-Watel, Patrick; Gagneux-Brunon, Amandine; Botelho-Nevers, Elisabeth; Sanchez, Alvaro; Gauna, Fatima; Fressard, Lisa; Bonneton, Marion; Launay, Odile; Ward, Jeremy K.
ABSTRACT: The French health authorities extended vaccination against COVID-19 to adolescents in June 2021, during the epidemic resurgence linked to the delta variant and because of insufficient vaccination coverage to ensure collective protection. In May 2021, we conducted a national online cross-sectional survey of 2533 adults in France to study their attitudes toward COVID-19 vaccines and their acceptance of child/adolescent vaccination according to targeted age groups (<6 years; 6–11; 12–17) and its determinants. We applied a multi-model averaged logistic regression for each of these age groups to study the determinants of favorability to vaccination. Among the respondents, 62.7% (1597) accepted COVID-19 vaccination for adolescents, 48.3% (1223) for children aged 6–11 years, and only 31% (783) for children under 6 years. Acceptance increased with fear of contracting COVID-19 and trust in institutions and decreased as the COVID-19 vaccine risk perception score increased. People favorable to vaccination in general and those sensitive to social pressure were also more often favorable to vaccinating children/adolescents than those who were not. Drivers of acceptance were ranked differently for the different age groups. Understanding these differences is essential to anticipating obstacles to vaccination of these age groups and designing appropriate information and motivational strategies to support it.